ANALYZING STUDENTS’ MATHEMATICAL REASONING IN SOLVING PROBABILITY PROBLEMS THROUGH SPIN THE WHEEL-ASSISTED WORKSHEETS - Sa’adah, Aliyatus; Lailiyah, Siti; Setyawati, Maunah (Jurnal Numeracy, 2025)
Mathematical reasoning ability is an essential aspect of mathematics learning because it helps students understand concepts and draw logical conclusions. However, many studies have shown that this ability remains low due to learning that is overly focused on procedures. Therefore, it is necessary to use engaging learning media that can help students connect abstract concepts with real experiences. This study aims to analyze students’ mathematical reasoning ability on the topic of probability using worksheets (LKPD) assisted by Spin the Wheel media. The research employed a descriptive qualitative approach involving three eighth-grade students of SMPN 2 Waru, selected based on high, medium, and low reasoning categories. Data were collected through essay tests, observations, and interviews, and analyzed using four indicators of mathematical reasoning: (1) constructing sample spaces and determining probabilities, (2) making predictions, (3) comparing theoretical probabilities with experimental results, and (4) drawing logical conclusions. The results show that students’ mathematical reasoning ability falls into the moderate category, with the main difficulty found in comparing theoretical and experimental results. The Spin the Wheel media effectively helps students understand probability concepts more concretely and increases their learning engagement. However, teacher guidance is still needed to help students connect experimental findings with theoretical concepts.